Synergistic strategy constructed novel double-network scaffolds with active micro-environment pH stabilization and M2-macrophage polarization for cartilage defect repair. (1st June 2023) - Zou, Faxing; Meng, Haoye; Ma, Mengjiao; Han, Feng; Wang, Yansen; Xie, Yajie; Yang, Jiayu; Wei, Shuai; Choinska, Emilia; Peng, Jiang; Zheng, Yudong
Abstract: Due to the disorder in microenvironmental pH, the persistence in inflammation, and the incomplete structural functionality of the healing cartilage-bone interface, cartilage defect repair has become a serious issue that needs to be addressed urgently. Therefore, a promising approach for treating cartilage defects would be to create multifunctional cartilage scaffold capable of stabilizing pH in the microenvironment, reducing inflammation, and promoting healed structural integrity in joint. Herein, the cartilage scaffold (M-APUs) consisting of amino acid-based polyurethane and modified chitosan was constructed to achieve synergistic therapy through creating a congenial microenvironment, supporting stem cell adhesion and growth, and enhancing normal remodeling of the osteochondral interface. The APU features stabilizing the pH of the microenvironment during its biodegradation, providing a comfortable environment for cartilage repair. Besides, the MC could help to stabilize scaffold structure, which could be enhance the promotion of cartilage repair. The cartilage scaffold was verified in an animal model, and the results demonstrated that the M-APUs could prevent deterioration of articular cartilage and promote cartilage repair. Moreover, histologic ICRS score of healed cartilage increase significantly and the integrity of structure and functionality about joint were greatly improved. It can be speculated that the novel system constructed with the synergistic strategy could become a competitive biomaterial in cartilage damage treatment. Graphical abstract: Image 1 Highlights: The APU in M -APUs endows composite with excellent pH stabilization in microenvironment. The M -APUs could accelerate the macrophages polarization into anti-inflammatory M2. The M -APUs could significantly induce stem cell adhesion, growth and migration. The M -APUs could improve the integrity of structure and functionality about joint.